Implementasi Rencana Tata Ruang Wilayah Kota Semarang - Cahyo Adhi Widodo; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2017)
Urban Land use Plan of Semarang need to be studied further to see location of demographic Semarang City which make Semarang City developed become city that focusing on trade and service, and density of population of Semarang City which increasingly dense every year, in order to make Semarang City as center of international trade and service that is safe, convenient, productive, and sustainable. However, various strategic issues that developed are the high land conversion, the illegal construction of illegal buildings and the placement of development status that is not in accordance with the spatial layout of Semarang City Government, as happened in Genuk Subdistrict, the development of industrial number in Genuk resulted in the increasing of industrial activity that have impact on environmental quality, industrial pollution cases can also be attributed to a lack of knowledge of waste treatment. Therefore, this study aims to find out the implementation of Urban Planning and Regional Planning of Semarang city as well as the driving factors and inhibiting factors faced by Semarang City Government in implementing Urban Plans and Regional Plans of Semarang City. Analytical techniques to obtain data through interviews with informants, observation, and supporting documents. This research uses the theory of George Edwards III (1980) can be seen that the implementation of the policy is influenced by four factors such as: communication, resources, position and bureaucratic structure. The results of this study indicate that the Implementation of Spatial Planning and Regional Planning of Semarang city seen from "five right" it is said that in the policy accuracy has been running effectively and very well; Accuracy of the implementer, the implementer is ready to implement the policy; Target precision, is very suitable; But in environmental preciseness there are still constraints because there is poor communication between government and society; And in the accuracy of the process, the implementation of the spatial plan of the program implementers is ready. The recommendations are to increase the intensity of information dissemination to the community, and to expand the media used in the delivery of information so that all levels of society can find out the latest info, improve performance and expand their insights and resources by conducting comparative studies.